(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
North American suffragettes were a landmark in the history of the rights for women, and, as well as it happened in Europe, suffered the strong reaction from the male elites. Literature, social science, art, developed an antifeminist discourse, called Romantic Misogyny, as a defense against women’s ambition of equality, trying to convince that femininity is only reached in love and marriage. The Bostonian written by Henry James (1886) belong to this antifeminist strategy, although it constitutes a record of the difficulties for suffragettes at the time, and a good evidence of the coarse purposes against women political actions.